Present-day conservative treatment retinopathy of prematurity - Modrzejewska, Monika; Kubasik-Kładna, Katarzyna; Kuprjanowicz, Leszek (Klinika Oczna / Acta Ophthalmologica Polonica, 2013)
Retinopathy of prematurity occurs in prematurely born babies. Etiology of disease is multifactorial and frequency of retinopathy of prematurity diagnosis increases. Retinopathy is one of causes for major loss of vision and amaurosis in newborns around the world. Low efficacy of treatment leads to necessity for looking for new solutions and modern therapy use in treatment of this disease. So far, therapies used are: laser and cryotherapy and cases of retina detachment, the course is combined with surgical procedures of sclera and vitrectomy. The aim of the paper was detailed observation of available literature concerning new methods of management in retinopathy of prematurity. Newest reviews on role of vascular endothelial growth factor secreted under the influence of hypoxia indicate that it takes part in angiogenesis and neovascularization. Thus, in retinopathy of prematurity management vitreous application of vascular endothelial growth factor inhibitors such as ranibizumab, bevacizumab are used as supplement or treatment combined with laser therapy or surgical procedures, however there are many controversies on this form of treatment. Recently there has been an interest in vitreous application of Triamcinolon and other experimental substances inhibiting fibro-vascular proliferations in mouse models of retinopathy of prematurity. Hopes connected with high efficacy of retinopathy of prematurity treatment are also related to use of gene therapy, b-blockers, supplementation with Omega-3 acids, matrix metalloproteinase-2 inhibitors, gold nanoparticles-GNP and anthrax lethal toxin.